Antioxidatant Effect of Atorvastatin and Rosuvastatin in Hyperlipidemic Patients: A Randomized Controlled Trial (Journal of Armed Forces Medical College, Bangladesh, 2019)
Introduction: Hyperlipidemia is a major risk for the development of atherosclerosis leading to cardiovascular complications. Atorvastatin and rosuvastatin are two widely used important members of the HMG-CoA reductase inhibitor (statins). The beneficial effects of statins on clinical events also involve lipid-independent mechanisms which include improvement of oxidative stress status.Objective: To compare the antioxidative effect of atorvastatin and rosuvastatin in patients with hyperlipidemia.Materials and Methods: A prospective randomized single-center analytic study was carried out in Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka from March 2016 to August 2017 on 52 hyperlipidemic patients. After randomization patients were assigned to atorvastatin 10 mg or rosuvastatin 5 mg daily for 8 weeks. Blood was collected at baseline and after the intervention to measure plasma malondialdehyde (MDA), erythrocyte reduced glutathione (GSH) (as biomarkers of oxidative stress) and serum lipid profile.Results: The baseline characteristics of patients treated with atorvastatin and rosuvastatin were almost identical. The level of plasma MDA in atorvastatin (1.35 ± 0.94 to 0.97± 0.64) and rosuvastatin (1.56±0.69 to 0.98±0.38) group was significantly reduced after intervention (28.15%, p